Argument-Driven Inquiry, Gender, and Its Effects on Argumentation Skills - Hasnunidah, Neni; Wiono, Wisnu Juli (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
Argumentation is considered by science teachers as a major component of science education. Middle school students need to be empowered in their argumentation skills to answer challenges to global competition. This study aimed to compare the argumentation skills between male and female students in science through the Argument-Driven Inquiry (ADI) model and guided inquiry model. There were 317 participants (150 male and 167 female) eighth-grade students of several schools in Bandar Lampung. The Pretest-posttest Non-equivalent Control Group Design was used as a part of a quasi-experimental design. The experiment class applied the ADI model and the control class applied the guided inquiry model. The data were collected by argumentation test, questionnaire of implementation learning syntax, and participant’s response. The data were analyzed by ANCOVA test and qualitative techniques. The results indicated that the ADI model led to a significant increased in argumentation skills in the science context. Moreover, there is no difference in the achievement of females and males. When students were encouraged to state claims and support their claims with data, warrants, and backing, it was observed that their argumentative discourse increased in terms of both the structure and the complexity of the argumentation. In light of the findings, it is suggested that the argumentation activities should be developed to promote students' science content knowledge and argumentation skills of both male and female students.